2016
DOI: 10.4172/2329-6674.1000142
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anterior Open Bite among Sample of Sudanese University Students

Abstract: Approval letter from the Ethical committee of the university of Abstract Objective: The aims of this study were to determine the prevalence and etiological factors of anterior open bite in the permanent dentition in a sample of Sudanese university students. Materials and methods:A cross section study for 1224 Sudanese university students (612 males and 612 females), age ranges between 17 and 23 years old. Anterior open bite was registered when there was lack of contact between the anterior teeth while the post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…43 The present study also revealed that the prevalence of anterior open bite was 21.6%, which is high compared to a study done in Sudan (8.5%). 44 This might be due to the difference in ethnicity and environmental factors among the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…43 The present study also revealed that the prevalence of anterior open bite was 21.6%, which is high compared to a study done in Sudan (8.5%). 44 This might be due to the difference in ethnicity and environmental factors among the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal AOB is marked by specific anatomical characteristics, including an overlarge mandibular plane angle, gonial angle, anterior facial height, and total facial height as well as an anteriorly upward-tilting palatal plane and a retrognathic mandible. 10 , 11 Skeletal AOB can be caused by several factors that disrupt the growth patterns of the maxillae, mandible, and dentoalveolar complex, such as a hereditary predisposition, developmental disorder, and history of trauma. 12 , 13 These disruptions contribute to the hyperdivergence of inter-base angles, resulting in an augmented posterior vertical dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Anterior open bite is considered to be one of the most challenging dentofacial deformities to treat due to the difficulties in determining the causes, formulating a diagnosis and the potential for relapse after treatment. [2][3] Open bite can be simple without abnormal measures to the vertical cephalometric analysis or complex with disharmony in the skeletal components of the anterior facial height. It is usually associated with Class I, II or III skeletal discrepancies.…”
Section: Introductionmentioning
confidence: 99%